Electromagnetic Wave Scattering from a Wedge with Perfectly Reflecting Boundaries: Analysis of Asymptotic Techniques - Hacivelioglu, Feray; Sevgi, Levent; Ufimtsev, Pyotr Ya. (IEEE-Inst Electrical Electronics Engineers Inc, 2011)
High-frequency asymptotic (HFA) techniques are reviewed through a classical, canonical problem: electromagnetic wave scattering from a wedge-shaped object with perfectly electrically conducting (PEC) boundaries. The Physical Optics (PO) and Physical Theory of Diffraction (PTD) approaches are compared against the exact solution through many scenarios and illustrations.
Keywords: Electromagnetic scattering; diffraction; geometrical optics wedge diffraction; exact series; exact integrals; physical optics; physical theory of diffraction; high frequency asymptotics; numerical integration; saddle point evaluation; steepest descent path integration